FAKTOR PENGHAMBAT ADOPSI INOVASI BUDIDAYA LEBAH MADU KLANCENG DI DESA MENDOLO KECAMATAN LEBAKBARANG KABUPATEN PEKALONGAN - Prasetyo, Eko; Sugiarto, Mochamad; Hilmi, Endang; Muslihudin, Muslihudin; Rahab, Rahab; Sari, Lilik Kartika (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
The traditional practice of Stingless honey hunting, which has been carried out for generations, tends to damage the forest ecosystem. The adoption of more environmentally friendly Stingless honey bee cultivation innovations began 10 years ago, resulting in 25 adopters out of 377 farmers at Mendolo Village, Lebakbarang District, Pekalongan Regency. This study aims to identify the inhibiting factors in the adoption process of Stingless honey bee cultivation innovations. The research was conducted using qualitative methods through observation, interviews, documentation, and focused group discussions. The results of the study show that the inhibiting factors for adopting Stingless honey bee cultivation include difficulty in finding colonies, pests, lack of knowledge about cultivation techniques, colony escape, limited food supply during the rainy season, lack of patience, low income, capital issues, colony transfer process, lack of colony splitting skills, urgent needs, harvesting methods, theft and vandalism, time constraints, lack of interest, market saturation during the harvest season, and influence from certain individuals. Key words:   Inhibiting Factors, Innovation Adoption, Stingless Honey Bee